Multidrug-Resistant Bloodstream Infections in Internal Medicine: Results from a Single-Center Study. Issue 5 (May 2022) - Pace, Edoardo; Bracco, Christian; Magnino, Corrado; Badinella Martini, Marco; Serraino, Cristina; Brignone, Chiara; Testa, Elisa; Fenoglio, Luigi Maria; Porta, Massimo
Abstract : Infections caused by multidrug-resistant organisms are expanding globally and they are associated with higher mortality rates and hospital-related costs. The authors performed a retrospective, case-control, single-center study. Studies in the literature often refer to general hospital populations or intensive care patients, whereas the authors' study is the first to analyze risk factors for multidrug-resistant bacteria in the complex setting of an internal medicine department. Abstract: Objectives: Infections due to multidrug-resistant organisms (MDROs) are expanding globally and are associated with higher mortality rates and hospital-related costs. The objectives of this study were to analyze the trends of MDRO bacteremia and antimicrobial resistance rates in Internal Medicine wards of our hospital and to identify the variables associated with these infections. Methods: During a 6-year period (July 1, 2011–June 30, 2017), patients with positive blood culture isolates hospitalized in the Internal Medicine wards in the Santa Croce and Carle Hospital in Cuneo, Italy, were assessed. We performed an analysis taking into consideration the time trends and frequencies of MDRO infections, as well as a case-control study to identify clinical-demographic variables associated with MDRO bacteremias. Results: During the study period a total of 596 blood cultures were performed in 577 patients. The most frequently identified organism was Escherichia coli (33.7%), followed by Staphylococcus aureus (15.6%) and S epidermidis (7.4%). The percentage of resistance to methicillin among S aureus isolates showed a decreasing trend, whereas rates of extended-spectrum β-lactamase-producing Enterobacteriaceae and carbapenemase-producing Klebsiella pneumoniae increased during the study period. Multivariate analysis showed that the nosocomial origin of the infection, hospitalization during the previous 3 months, residence in long-term care facilities, presence of a device, antibiotic exposure during the previous 3 months, and cerebrovascular disease were independently associated with bacteremia by resistant microorganisms. Conclusions: Our analysis reveals a concerning microbiological situation in an Internal Medicine setting, in line with other national and regional data. The risk variables for infection by MDRO identified in our study correspond to those reported in the literature, although studies focused on Internal Medicine settings appear to be limited.